Comparative Study on the Performance of Different Lead‐Based and Lead‐Free Perovskite Solar Cells. Issue 5 (25th March 2021) - Jayan K., Deepthi; Sebastian, Varkey
Abstract: A comparative theoretical study on the performance of perovskite solar cells (PSCs) with methyl ammonium lead iodide (MAPbI3 ) and methyl ammonium germanium iodide (MAGeI3 ) as absorber layers is reported by modeling the solar cells for a number of electron transport materials (ETMs), hole transport materials, and back‐contact metals using solar cell capacitance simulator 1D tool. For MAPbI3 as the absorber layer, the best photovoltaic performance is observed for the configuration glass/fluorine‐doped tin oxide (FTO)/SnO2 /MAPbI3 /NiO/Au with a power conversion efficiency (PCE) of 20.58% and a fill factor (FF) of 68.34% and for MAGeI3, the configuration glass/FTO/SnO2 /MAGeI3 /CuO/Pd exhibits the best performance with a PCE of 13.12% and a FF of 68.29%. This study indicates that the low‐cost metal oxide SnO2 is a better substitute for the commonly used TiO2 as ETM, and the metal oxides like NiO and CuO provide a higher PCE for device configurations with MAPbI3 and MAGeI3, respectively, as the absorber layer. The low‐cost back‐contact metal Pd provides a better performance for MAGeI3 ‐based PSCs. This study also indicates that the nontoxic MAGeI3 ‐based PSCs can be used for commercial applications as they are more thermally stable than the MAPbI3 ‐based PSCs and provide an equally good quantum efficiency curve as that of MAPbI3 ‐based PSCs. Abstract : In this study, optimized solar cell configurations are obtained by modeling solar cells for a number of electron transport materials, hole transport materials, and back‐contact metals with either MAPbI3 or MAGeI3 as absorber layers using SCAPS 1D tool. The study identifies SnO2, NiO and CuO as suitable transport materials. The low‐cost back‐contact metal Pd provides better performance.